Erosion of Expenditure Management System : An Unintended Consequence of Donor Approaches - Premchand, A. (Washington, D.C. : International Monetary Fund, 1996)
The paper considers the various procedures and practices relating to budgeting and accounting of foreign aid, and points out that as a result of the high degree of ringfencing associated with the aid, a kind of functional dyarchy has emerged with serious implications for expenditure management in the recipient countries. It concludes that more structured negotiations, improved information systems as well as performance agreements have the potential of avoiding the problems now encountered.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet